Unlawful Acts and Legal Bullying: A Normative-Empirical Juridical Analysis of Case No. 1206/PDT.G/2025/PN JKT.BRT - I Nyoman Suandika; Hanphie Agusoeito (Journal of World Science, 2026)
This research analyzes two issues: first, the harmonization of norms between the provisions of unlawful acts (PMH) Article 1365 of the Civil Code and the instrument for the protection of the right to information in determining the limits of legitimate educational expression; second, the qualification of a lawsuit based on Article 1365 of the Civil Code against financial educators on social media as onrechtmatige procesvoering/misbruik van recht. The research uses normative-empirical juridical methods with legislative, conceptual, case, and comparative approaches, focusing on Case Number 1206/Pdt.G/2025/PN Jkt.Brt, PT. Tunas Tangkas Primaraga Sakti against financial educator Apriliana. The results of the study show that Article 1365 of the Civil Code does not provide an operational definition of the element of "unlawful", thus opening up space for expansive interpretation that has the potential to override the constitutional right to information according to Article 28F of the 1945 Constitution of the Republic of Indonesia in conjunction with Article 19 of the ICCPR. The a quo lawsuit meets three indicators of legal bullying: formal defects (ultra vires mandati and error in persona), disproportionate claim value (Rp3,654,182,500 without an accountable methodology), and indications of intimidation through a request for security confiscation of the defendant's private house. The mention of a trademark in educational content is qualified as a valid nominative fair use because it does not meet the elements of trademark use in trade according to Law Number 20 of 2016.